Molecular Typing of Neisseria gonorrhoeae Isolates by Opa-Typing and Ribotyping in New Delhi, India. (6th August 2009) - Khaki, Pejvak; Bhalla, Preena; Fayaz, Ahmad Mir; Moradi Bidhendi, Sohiela; Esmailzadeh, Majid; Sharma, Pawan
Abstract : Control and preventive measures for gonococcal infections are based on precise epidemiological characteristics of N. gonorrhoeae isolates. In the present study the potential utility of opa-typing and ribotyping for molecular epidemiological study of consecutive gonococcal strains was determined. Sixty gonococcal isolates were subjected to ribotyping with two restriction enzymes, Ava II and Hinc II, and opa-typing with Taq I and Hpa II for epidemiological characterization of gonococcal population. Ribotyping with Ava II yielded 6 ribotype patterns while twelve RFLP patterns were observed with Hinc II. Opa-typing of the 60 isolates revealed a total 54 opa-types, which 48 were unique and 6 formed clusters. Fifty-two opa-types were observed with Taq I-digested PCR product while opa-typing with Hpa II demonstrated 54 opa-types. The opa-types from isolates that were epidemiologically unrelated were distinct, whereas those from the sexual contacts were identical. The results showed that opa-typing is highly useful for characterizing gonococcal strains from sexual contacts and has more discriminatory than ribotyping that could differentiate between gonococci of the same ribotype. The technique even with a single restriction enzyme has a high level of discrimination (99.9%) between epidemiologically unrelated isolates. In conclusion, the molecular methods such as opa-typing and ribotyping can be used for epidemiological characterization of gonococcal strains.